Participación del empleado en la mejora continua = Continuous improvement through employee’s participation. - Cruz Álvarez, Jesús Gerardo (Universidad Autónoma de Nuevo León, 2007)
Abstract. In this paper we will discuss about the continuous improvement effect driven by the active employee participation. This will lead to have multiple results in innovation, problem solving and process optimization fields. We will discuss in regards of the main need of all organization to become more productive and efficient in order to promote a positive change, as well as the different alternatives that the firm can use in order to promote such change. We will propose Monozukury system and its tools like one of the most advanced system than can combine both aspects: Employee participation and positive change, both aspects supporting each other. This paper is divided in two manuscripts: The first includes a theoretical discussion about: 1) The need of change, 2) Employee satisfaction and quality culture, 3) Case of study: Automotive industry experience. The second manuscript will cover an empirical research about the cause and effect variables covered in this paper. The aim of this paper is to discuss about the employee relevant role and how it can be improved looking toward driving a positive change in all organizations.